PENGARUH KOMPENSASI, PELATIHAN, MOTIVASI TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH KESEIMBANGAN KEHIDUPAN KERJA PADA PERUSAHAAN PENGOLAHAN UANG RUPIAH ARTHALESTARI - Irene Putri Jauri; Hery Winoto; Melitina Tecoalu (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of compensation, training, motivation on employee performance at PT ArthaLestari. This study aims to determine the effect of training on the performance of PT Artha Lestari employees, the influence of motivation on the performance of PT ArthaLestari employees, the effect of compensation on employee performance mediated by work-life balance, the effect of training on employee performance mediated by work-life balance, the influence of motivation on employee performance mediated by work-life balance.The research model used is a survey method with a quantitative approach, namely by emphasizing hypothesis testing. The sample of this study was 171 employees of PT ArthaLestari. Sampling method with Likert Scale Method.